1997
DOI: 10.1093/humrep/12.7.1550
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of oocytes and embryos: use of a mouse model to investigate effects upon zona hardness and formulate treatment strategies in an in-vitro fertilization programme

Abstract: Mouse oocytes and embryos were obtained following ovulation induction of (C57B16 x CBA) F1 animals. Zonae pellucidae were exposed to alpha-chymotrypsin in phosphate-buffered medium (PB1) supplemented with 3 mg/ml bovine serum albumin upon a heated stage (37 degrees C) and were observed constantly through an inverted microscope. The endpoint of the bioassay was the limits of the zona no longer being seen clearly at x 200 magnification, and the time taken for each zona to dissolve was recorded. A dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 14 publications
2
41
0
3
Order By: Relevance
“…The observation here is that cleavage rates are similar between study groups in ICSI but very different when IVF is used. The most probable reason for this is the effect of cryopreservation on zona pellucida hardening, which has been previously proven by molecular studies [4,11,13]. Oocyte degeneration was higher in the slow-freezing group implying occult damage, caused by this method of cryopreservation, escaping the initial inspection for survival and this was an observation in both experiments.…”
Section: Resultssupporting
confidence: 55%
“…The observation here is that cleavage rates are similar between study groups in ICSI but very different when IVF is used. The most probable reason for this is the effect of cryopreservation on zona pellucida hardening, which has been previously proven by molecular studies [4,11,13]. Oocyte degeneration was higher in the slow-freezing group implying occult damage, caused by this method of cryopreservation, escaping the initial inspection for survival and this was an observation in both experiments.…”
Section: Resultssupporting
confidence: 55%
“…Previous studies indicated that freezing of murine oocytes can result in zona pellucida hardening (Carroll et al, 1990;Matson et al, 1997), which was the primary cause of fertilisation failure (Carroll et al, 1990) of cryopreserved oocytes. Zona pellucida hardening during freezing-thawing could be due to premature release of cortical granule contents (Vincent et al, 1990), although others did not observe a change in cortical granules.…”
Section: Discussionmentioning
confidence: 99%
“…Zona-drilling (Carroll et al, 1990) or intracytoplasmic sperm injection (ICSI) (Gook et al, 1995) could overcome the blocking effect of zona pellucida hardening on fertilisation. Use of solutions containing FCS during cryopreservation prevented zona hardening (George et al, 1994), but the addition of human serum to the freezing solution for murine oocytes resulted in zona hardening (Matson et al, 1997). A recent study indicated that zona pellucida hardening was reduced and subsequent fertilisation significantly increased by carrying out vitrification in calcium-free media (Larman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chilling also induces premature cortical granule exocytosis that may cause zona hardening [25]. Hardening of the zona pellucida can adversely affect the normal fertilization process [26]. This change halts the sperm penetration of zona and inhibits embryonic hatching, but these problems can be overcome by intracytoplasmic sperm injection and assisted hatching [27][28][29].…”
Section: Cryopreservation Of Oocytementioning
confidence: 99%